Differently increased volumes of multiple brain areas in Npc1 mutant mice following various drug treatments - Antipova, Veronica; Heimes, Diana; Seidel, Katharina; Schulz, Jennifer; Schmitt, Oliver; Holzmann, Carsten; Rolfs, Arndt; Bidmon, Hans-Jürgen; González de San Román Martín, Estibaliz; Huesgen, Pitter F.; Amunts, Katrin; Keiler, Jonas; et al. (Frontiers in Neuroanatomy, 2024)
Background Niemann-Pick disease type C1 (NPC1, MIM 257220) is a heritable lysosomal storage disease characterized by a progressive neurological degeneration that causes disability and premature death. A murine model of Npc1−/− displays a rapidly progressing form of Npc1 disease, which is characterized by weight loss, ataxia, and increased cholesterol storage. Npc1−/− mice receiving a combined therapy (COMBI) of miglustat (MIGLU), the neurosteroid allopregnanolone (ALLO) and the cyclic oligosaccharide 2-hydroxypropyl-β-cyclodextrin (HPßCD) showed prevention of Purkinje cell loss, improved motor function and reduced intracellular lipid storage. Although therapy of Npc1−/− mice with COMBI, MIGLU or HPßCD resulted in the prevention of body weight loss, reduced total brain weight was not positively influenced. Methods In order to evaluate alterations of different brain areas caused by pharmacotherapy, fresh volumes (volumes calculated from the volumes determined from paraffin embedded brain slices) of various brain structures in sham- and drug-treated wild type and mutant mice were measured using stereological methods. Results In the wild type mice, the volumes of investigated brain areas were not significantly altered by either therapy. Compared with the respective wild types, fresh volumes of specific brain areas, which were significantly reduced in sham-treated Npc1−/− mice, partly increased after the pharmacotherapies in all treatment strategies; most pronounced differences were found in the CA1 area of the hippocampus and in olfactory structures. Discussion Volumes of brain areas of Npc1−/− mice were not specifically changed in terms of functionality after administering COMBI, MIGLU, or HPßCD. Measurements of fresh volumes of brain areas in Npc1−/− mice could monitor region-specific changes and response to drug treatment that correlated, in part, with behavioral improvements in this mouse model.